Planning Document for Employers: Changing Demographics of the Milwaukee Metro Labor Force - (:unkn) unknown (My University, 2004)
This report was prepared for employers, public policymakers, and educators to identify demographic trends that will affect the availability of labor for Milwaukee area companies in the next decade. Labor force changes are examined for the four-county Milwaukee metro area, utilizing detailed 2000 U.S. Census data and changes in hiring patterns (including occupational status by gender and race/ethnicity) based on reports filed by public and private employers with the U.S. Equal Opportunities Employment Commission.
Keywords: labor market information